The surprise attack of Jabba the Puppett - Angleberger, Tom. (New York : Amulet Books, 2013)
Dark times have fallen on McQuarrie Middle School. Dwight is back--and not a moment too soon--as Kellen, Sara, and the gang face a new Menace: the FunTime Educational Program. FunTime is supposed to raise students' standardized test scores. Instead, it's driving everyone crazy. The students turn to Origami Yoda for help.
Instructions for origami Jabba and Ewok inside!
School Library Journal, November 2013.
Horn Book, April 2014.
Kirkus Review, August 2013.
School Library Journal.
Horn Book.
Keywords: Yoda (Fictitious character : Lucas) -- Juvenile fiction; Finger puppets -- Juvenile fiction; Origami -- Juvenile fiction; Eccentrics and eccentricities -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Yoda (Fictitious character : Lucas) -- Fiction; Finger puppets -- Fiction; Origami -- Fiction; Eccentrics and eccentricities -- Fiction; Interpersonal relations -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Yoda (Fictional character : Lucas) -- Fiction; Puppets and puppet plays -- Fiction; Origami -- Fiction; Eccentrics and eccentricities -- Fiction; Interpersonal relations -- Fiction; Middle schools -- Fiction; School stories; Finger puppets -- Fiction; Origami -- Fiction; Eccentrics and eccentricities -- Fiction; Interpersonal relations -- Fiction; Middle schools -- Fiction